Analisis Efisiensi Usaha Pembesaran Ikan Nila di Desa Marga Sakti Kecamatan Padang Jaya Kabupaten Bengkulu Utara - Cahyati, Ainun; Yuristia, Rahmi; Sumantri, Bambang (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2022)
North Bengkulu Regency is one of the freshwater fishery producing areas in Indonesia  Bengkulu Province. Forty percent of Bengkulu Province's total freshwater fish production  is from North Bengkulu. The fishery center in North Bengkulu is in the District of  Padang Jaya and has been designated as a freshwater fishery Minapolitan area. Type  Tilapia (Oreochromis niloticus) is one type of fish that is in great demand  by the community to be cultivated, because Tilapia has sufficient tolerance  high relative to the environment as well as its relatively fast growth. Purpose  This research is: (1) Analyzing the amount of business income Tilapia  and, (2) Analyzing the efficiency level of Tilapia rearing business. Determination of the location in  this research was conducted intentionally (purposive). The population in this field study is  tilapia farmers totaling 150 farmers. Determination of the number of respondents in the field study  This is the Simple Random Sampling method. The average value of Tilapia fish production in  Marga Sakti Village is 1.817 Kg/MT so that the total revenue received by farmers  Tilapia an average of Rp. 33.608.333/ MT and the value of fish farmers' income  The average tilapia in Marga Sakti Village is Rp. 18,192,229/MT. So that the value of  The average R/C ratio per stocking season is 2.28. This shows that the effort  Tilapia cultivation with a calm water pond system in Marga Sakti Village is categorized as suitable for cultivation  cultivated because the amount of expenditure on cultivation business costs is smaller than  with acceptance.